Peluang dan Tantangan : Penggunaan Media Digital di Kalangan Perempuan Jatinangor - Eni Maryani; Kismiyati El Karimah (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2019)
The discussion of digital media usage in various societal contexts is a necessity that cannot be avoided since it has both positive and negative impacts. This article will raise the issue of digital media usage by women in Jatinangor. Jatinangor is an educational area on the east side of Bandung and including the Sumedang Regency area. Jatinangor has quite dynamic social economic development and has experienced a significant change with the number of student arrivals in the area. The development of communication technology infrastructure also has implications for the growing use of digital media among women in the Jatinangor area. Using a qualitative approach with in-depth interviews observation and literature studies, this study seeks to uncover the implications of digital media among Jatinangor women related to patriarchal values that generally affect women's thoughts, attitudes and actions. The results of the study show that there are opportunities for women who use digital media to overcome some cultural barriers in gaining communication space for themselves, especially in the public domain. However, the use of digital media also challenges these women to develop selective, critical and rational attitudes that are not familiar for them. The lack of these attitudes can actually make these women objects or targets of various commercial and criminal communication activities.